PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP HASIL BELAJAR IPS SISWA SMP NEGERI 13 PEKANBARU - Rita Novita; Sumarno '; Hardisem ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Education is the way to lift social status in society and asset to reach better life and better future. In addition, education is also expected to hone skill and ability to face and solve the problems quick and accurate. With school, people can achieve the necessity of education. In school, people who success in learning will get appreciation from community. Not only the School, Family have important role to get success in learning. Family is the first place people learning, where parents be the very first teacher. This study aimed to determine whether there are significant socio-economic status of parents to student learning outcomes social sciences SMP 13 Pekanbaru. This research is located on the road Ronggowarsito I No. 15 SMP Negeri 13 Pekanbaru. The data obtained from the school SMP 13 Pekanbaru form of learning outcomes (value of report books second semester of the 2015/2016 academic year) in IPS study. The technique used is systematic sampling technique so that the sample amounted to 75 peoples. The analysis used was multiple linear regression analysis to determine the effect of socio-economic status of parents on learning outcomes. From the results of the analysis, there is a significant influence between social economic status parents to learning outcomes. The results of this study can be taken into consideration for schools and parents to pay more attention to the development of students' learning conditions, because schools and parents have a very important role in improving student learning outcomes.Key Words: socio-economic status of parents and Learning Outcomes